Antibiotic Sensitivity in Post Cesarean Surgical Site Infection at a Tertiary Care Centre in Eastern Nepal - Manisha Chhetry; Shanti Subedi; Sita Ghimire; Sabina Lamichhane; Basudev Banerjee; Ganesh Kumar Singh (Journal of Lumbini Medical College, 2016)
Introduction: Post cesarean surgical site infection (SSI) is one of the common complications diagnosed in 2.5%-16% of the cases and is associated with significant increase in maternal morbidity, hospital stay, costs, and psychological stress to the new parents. This study was designed to study the incidence of SSI and the antimicrobial resistance pattern in our hospital.